Ibu Ni Gusti Ayu Kartika TUMPEK WARIGA SEBAGAI KEARIFAN EKOLOGIS DALAM TRADISI RITUAL MASYARAKAT HINDU BALI: TUMPEK WARIGA SEBAGAI KEARIFAN EKOLOGIS DALAM TRADISI RITUAL MASYARAKAT HINDU BALI - Kartika, Ni Gusti Ayu (Sphatika: Jurnal Teologi, 2026)
Tumpek Wariga is one of Bali’s local wisdom traditions that is traditionally practiced through religious rituals by the Hindu community. This ceremony emphasizes the harmonious relationship between humans, nature, and God, particularly in the context of preserving vegetation and local ecosystems. This study employs a qualitative approach using ethnographic methods, including participant observation and in-depth interviews with traditional leaders, priests, and community members involved in the ritual practices in Bali. The analysis is conducted through symbolic, ecological, and ritual performance frameworks to understand the ecological meanings embedded in the Tumpek Wariga practice. The findings reveal that this ceremony functions not only as a religious manifestation but also as a mechanism for cultural and environmental conservation. Tumpek Wariga encourages sustainable plant maintenance, local ecosystem management, and the intergenerational transmission of ecological values. Therefore, this ritual represents a concrete manifestation of Bali’s local genius, integrating religious, ecological, and social aspects in cultural and environmental preservation. These findings contribute significantly to the understanding of local wisdom as an adaptive strategy in responding to the dynamics of globalization, as well as to the recognition of intangible cultural heritage with high ecological value.